The efectiveness of maintenance management of the mosque / Muhammad Nazif Baharuddin - Baharuddin, Muhammad Nazif (2016)
The mosque is one of the unique buildings in Malaysia. Building structures, domes and towers on the mosques enough to show the features and Islamic identity. The main role of the mosque as a meeting place for Muslims, the administrative center and the diffusion of knowledge and zakat collection centers. However, the maintenance of the mosque not care by the mosque management and Religion Council. A study was carried out through the collection of information and data from interviews and questionnaires. This study was conducted at two mosques, which Masjid Muhammadi, Kota Bharu and Masjid Al-Sultan Ismail Petra, Kubang Kerian. The objective of this study is to identify the types of maintenance that was carried out at the mosque, to investigate of the damage complaint system at the mosque and to determine the level of user comfort against the maintenance management system conducted in the mosque. Questionnaires were distributed at both of the mosques. The results of the analysis found that the type of maintenance often performed is routine maintenance. While, damage reporting system is through direct meetings with the management of the mosque is more effective. The satisfaction level of respondents at the Masjid Muhammadi is satisfactory. While at the Masjid Al-Sultan Ismail Petra at less satisfactory level.